2020
DOI: 10.1111/sode.12480
|View full text |Cite
|
Sign up to set email alerts
|

Children’s sociomoral judgements of antisocial but not prosocial others depend on recipients’ past moral behaviour

Abstract: This study investigated whether recipients' past moral or immoral behaviour shapes 4-year-olds' judgements of the agents who either harm or help the recipients. Children (N = 161) watched the agent who either harmed or helped the antisocial, prosocial, or neutral recipient. Afterwards, children indicated their sociomoral judgement of the agent's act, their attitude towards the agent and their perception of the agent's emotions. Children liked the agent more, ascribed less sadness to the agent, and judged the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
(78 reference statements)
1
6
0
Order By: Relevance
“…Second, according to RRT, moral judgments should be understood as a manifestation of different social relationship motives (Rai & Fiske, 2011). We know that infants (Hamlin & Wynn, 2011; Hamlin et al, 2007) and preschoolers (Bocian & Myslinska Szarek, 2020; Li & Tomasello, 2018; McAuliffe et al, 2015; Smetana & Ball, 2018; Smetana et al, 2014) do not have a simple aversion to individuals who harm third parties, but rather consider whether harmful actions were justified, which suggests that they are capable of making complex social judgments. For example, a recent study had demonstrated that 4‐year‐old children judged harmful behavior as less bad when the behavior was directed at the antisocial recipient than at the prosocial recipient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, according to RRT, moral judgments should be understood as a manifestation of different social relationship motives (Rai & Fiske, 2011). We know that infants (Hamlin & Wynn, 2011; Hamlin et al, 2007) and preschoolers (Bocian & Myslinska Szarek, 2020; Li & Tomasello, 2018; McAuliffe et al, 2015; Smetana & Ball, 2018; Smetana et al, 2014) do not have a simple aversion to individuals who harm third parties, but rather consider whether harmful actions were justified, which suggests that they are capable of making complex social judgments. For example, a recent study had demonstrated that 4‐year‐old children judged harmful behavior as less bad when the behavior was directed at the antisocial recipient than at the prosocial recipient.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study had demonstrated that 4‐year‐old children judged harmful behavior as less bad when the behavior was directed at the antisocial recipient than at the prosocial recipient. More importantly, children also displayed a positive attitude toward individual who harmed antisocial other and negative attitude toward individual who harmed prosocial other (Bocian & Myslinska Szarek, 2020). Therefore, our studies confirm that in the context of beneficial relationships, young children's attitudes reflect their desire to sustain cooperation with the antisocial partner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, recent research has shown that when young children collaborate with partners who help them to acquire resources but also harm third parties, their obligation to sustain the beneficial relationship is stronger than the aversion to antisocial others. In the result, children express a positive attitude towards the partner, even though they recognize the partner's actions as immoral (Myslinska Szarek, Bocian, Baryla, & Wojciszke, 2020).…”
Section: Egocentric Evaluations Are Strategicmentioning
confidence: 99%
“…Only recently was the idea that automatic evaluations might bias people's judgements of others' actions directly tested. Specifically, studies have investigated how positive outcomes (e.g., personal benefits, group interests) and attitudes (e.g., liking) influence moral judgements of others' behaviour (Bocian, Baryla, & Wojciszke, 2016; Bocian, Cichocka, & Wojciszke, 2020b; Bocian & Wojciszke, 2014a, 2014b; Wojciszke & Bocian, 2018), and moral character judgements (Bocian, Baryla, Kulesza, Schnall, & Wojciszke, 2018; Bocian & Myslinska Szarek, 2020; Grizzard et al, 2020; Melnikoff & Bailey, 2018).…”
Section: Egocentrism Biases Moral Evaluations Of Others' Actionsmentioning
confidence: 99%